A Brief Review of Calibration-Free Laser-Induced Breakdown Spectroscopy - Zhang, Ning; Ou, Tianxue; Wang, Meng; Lin, Zhanjian; Lv, Chao; Qin, Yuzhi; Li, Jiaming; Yang, Huan; Zhao, Nan; Zhang, Qingmao (Frontiers in Physics, 2022)
The calibration-free laser-induced breakdown spectroscopy (CF-LIBS) technique requires no referenced samples of the same matrix to establish the calibration curve, not affected by the matrix effect. In recent years, CF-LIBS technology has a great progress, the accuracy of quantitative analysis has gradually improved. The purpose of this review is to introduce the CF-LIBS fundamental and modified algorithms. Boltzmann plot method, Saha-Boltzmann plot method, and column density Saha-Boltzmann plot (CD-SB) method were discussed. Moreover, as a critical factor in CF-LIBS, self-absorption effect and its influence on CF-LIBS were also introduced. CF-LIBS has been applied in a variety of fields, such as environmental protection, explorations of space, cultural heritage preservation, geological survey, which were also described in this review.